With strong WLE/Bioversity support, the EAT Lancet Commission study is transforming international food system and dietary guidelines for health and sustainability - CGIAR Research Program on Water, Land and Ecosystems (2019)
With four senior scientist co-authors, the CGIAR was a major contributor to the EAT-Lancet Commission’s ground-breaking comprehensive review defining a universal healthy diet. It also show how agriculture, currently the primary cause and victim of environmental degradation, is also our best bet for solving hunger, health and sustainability. The report is having a profound influence on the international development discourse and has set the stage for the work of the WLE Commission on the Sustainable Intensification of Agriculture.